2015
DOI: 10.1007/s11136-015-0985-8
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life changes in patients undergoing treatment for hepatocellular carcinoma

Abstract: There were significant differences in QoL deterioration across different treatment groups. This information may assist patients and providers when selecting patient-centered treatment approaches for HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 21 publications
1
21
0
1
Order By: Relevance
“…Moreover, patients had greater deterioration of cognitive functioning when they underwent RFA versus TAE/TACE from baseline to 6 months. These results were consistent with the previous study (Chie et al, ; Eid et al, ). This might be because that the TAE/TACE was a palliative treatment for unresectable LC and it has the potential for serious liver toxicity due to ischaemia and reperfusion and retention of chemotherapeutic agents (Trevisani, De Notariis, Rossi, & Bernardi, ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Moreover, patients had greater deterioration of cognitive functioning when they underwent RFA versus TAE/TACE from baseline to 6 months. These results were consistent with the previous study (Chie et al, ; Eid et al, ). This might be because that the TAE/TACE was a palliative treatment for unresectable LC and it has the potential for serious liver toxicity due to ischaemia and reperfusion and retention of chemotherapeutic agents (Trevisani, De Notariis, Rossi, & Bernardi, ).…”
Section: Discussionsupporting
confidence: 94%
“…There were several studies that investigated the specific factors associated with QoL. Chie et al found that patients tended to have higher odds of QoL deterioration when treated with ablation versus embolisation or ablation versus surgery (Chie et al, 2015). Kolligs et al (2015) also found that selective internal radiation therapy (SIRT) had a similar impact on QoL as multiple sessions of transarterial chemoembolisation (TACE).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, little research has examined suicide rates among US patients with esophageal and liver cancer, although each of these cancer types has an estimated 5‐year survival of less than 20% and may have quality‐of‐life concerns as a result of debilitating symptoms or treatment side effects . These cancers are also associated with alcohol and tobacco use, factors related to suicide risk in the general population .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Blazeby et al in 2012 and 2015 use this method of analysis in evaluating QoL after liver resection in colorectal cancer. 15,16 Morbidity Major morbidity and mortality were defined as intraoperative and postsurgical complications (9grade 2 according to the Memorial Sloan Kettering Cancer Center, MSKCC morbidity grading system) or death that occurred within 30 days after the surgical procedure. Major morbidity was divided into categories: infectious, gastrointestinal, cardiopulmonary, and thromboembolic complications.…”
Section: Pro Assessmentmentioning
confidence: 99%